KAJIAN KERAGAMAN GENETIK ANDALAS (MORUS MACROURA) UNTUK KONSERVASI GENETIK FLORA ASLI SUMATERA BARAT - Istiana Prihatini; AYPBC Widyatmoko; Maryatul Qiptiyah; Dodi Frianto; Eka Novriyanti (Jurnal Pemuliaan Tanaman Hutan, 2021)
Conservation management strategies for native Sumatran species such as andalas (Morus macroura) are currently being developed through genetic diversity studies. This genetic diversity information will be used to enhance ongoing conservation and regeneration programs and to control logging of this high value plant species. The aims of this initial study were to develop a method for extracting DNA from andalas cambium, to select polymorphic RAPD primers and to study genetic diversity using selected RAPD primers. DNA was successfully extracted using the CTAB method from all 32 cambium samples collected from Jambi and West Sumatra. Eighteen RAPD primers were screened and six polymorphic primers selected (OPO-6, OPY-6, OPY15, OPW-1, OPW-3 and OPW-4). RAPD analysis using the six selected primers resulted in 52 polymorphic loci and the value of genetic diversity within the population (Hs) of 0.308 and the value of genetic diversity among populations (DST) of 0.091. The highest genetic diversity was observed in Batipuah, Tanah Datar (0.351) and the lowest was observed in Halaban, Lima Puluh Kota (0.205). A test with AMOVA shows that the genetic diversity between individuals is greater than the diversity between populations. The dendogram based on the genetic distance between populations shows that the andalas population in West Sumatra is separated into two groups and both are separated from the Jambi population. The results of this study can be used as a basis for further research on several other andalas populations as well as the basic information for conservation strategies of andalas.